ALT Levels for Asians With Metabolic Diseases: A Meta‐analysis of 86 Studies With Individual Patient Data Validation. Issue 11 (9th September 2020) - Huang, Daniel Q.; Yeo, Yee Hui; Tan, Eunice; Takahashi, Hirokazu; Yasuda, Satoshi; Saruwatari, Junji; Tanaka, Kenichi; Oniki, Kentaro; Kam, Leslie Y.; Muthiah, Mark D.; Hyogo, Hideyuki; Ono, Masafumi; et al.
Abstract : The current alanine aminotransferase (ALT) upper limit of normal was defined using selected healthy Caucasian blood donors. Given the global rise in obesity and different body habitus in Asians, we aimed to perform a systematic review and meta‐analysis combined with bootstrap modeling and individual patient data validation to estimate the ALT upper threshold for Asians, including the overweight and diabetics. We included studies from PubMed, Embase, and Cochrane database searches that identified individuals without known liver diseases (i.e., viral hepatitis, alcohol, and ultrasound‐detected nonalcoholic fatty liver disease). The mean ALT (U/L) was estimated using a random‐effects mixed model and upper threshold (95th‐percentile value, U/L) via a bootstrap model with 10, 000 resamples. We screened 4, 995 studies and identified 86 studies that reported ALT values for 526, 641 individuals without excessive alcohol intake or known liver diseases, yielding a mean ALT of 19 and ALT upper threshold of 32. The ALT upper threshold was 37 in males versus 31 in females, 39 in overweight versus 28 in normal‐weight individuals, and 36 for diabetics versus 33 for nondiabetics. We validated our study level data with individual patient level data in 6, 058 individuals from five study centers in Japan. Consistent with our study‐level data, we found that the ALT upper threshold in our individual patient data analysis was indeed higher in overweight versus normal‐weight individuals (39 vs. 32) and in diabetics versus nondiabetics (42 vs. 33). Conclusion: We provide validated reference ranges for ALT upper threshold derived from Asians without known liver disease, including individuals with ultrasound‐detected nonalcoholic fatty liver disease who are normal weight, overweight, nondiabetic, and diabetic, to inform practice. Abstract : In this systematic review and meta‐analysis of 86 studies and 526, 641 individuals without viral hepatitis and hepatic steatosis, the ALT upper threshold was 39 in overweight patients versus 28 in normal‐weight individuals, and 36 in diabetics versus 33 in nondiabetics. These findings were validated in a multicenter cohort of 6, 058 patients. Diabetic and overweight patients with ALT values within these thresholds can potentially avoid extensive and possibly harmful invasive investigations after excluding viral hepatitis and nonalcoholic fatty liver disease. However, close monitoring and management of metabolic factors are required.